Seismic Rigoletto: Hazards, risks and seismic roulette applications - Bela, James; Kossobokov, Vladimir; Panza, Giuliano (Frontiers in Earth Science, 2023)
Neo-Deterministic Seismic Hazard Assessment (NDSHA), dating back to the turn of the Millennium, is the new multi-disciplinary scenario- and physics-based approach for the evaluation of seismic hazard and safety – guaranteeing “prevention rather than cure.” When earthquakes occur, shaking certainly does not depend on sporadic occurrences within the study area, nor on anti-seismic (earthquake-resistant) design parameters scaled otherwise to probabilistic models of earthquake return-period and likelihood – as adopted in the widespread application of the model-driven Probabilistic Seismic Hazard Analysis (PSHA). Therefore, from a policy perspective of prevention, coherent and compatible with the most advanced theories in Earth Science, it is essential that at least the infrastructure installations and public structures are designed so as to resist future strong earthquakes. Evidences and case histories detailed in the newly published Earthquakes and Sustainable Infrastructure (Panza et al, 2021) present a new paradigm for Reliable Seismic Hazard Assessment (RSHA) and seismic safety – comprehensively detailing in one volume the ‘state-of-the-art’ scientific knowledge on earthquakes and their related seismic risks, and actions that can be taken to ensure greater safety and sustainability. The book is appropriately dedicated to the centenary of Russian geophysicist Vladimir Keilis-Borok (1921-2013), whose mathematical-geophysical insights have been seminal for the innovative paradigm of NDSHA. This review focuses on Hazards, Risks and Prediction (Kossobokov, 2021), an understanding of which is essential in the applications of the state-of-the-art knowledge presented in the book’s 29 following chapters.